PRIMARY CLASS STUDENTS USING STEAM EDUCATION DEVELOPMENT OF CREATIVE THINKING - Gulbahor Pardaeva (International Journal of Innovations in Engineering Research and Technology, 2023)
Teaching SCIENCE at school in primary education helps to increase students’ knowledge about existence and the environment. Today, the development of continuous education and the introduction of international technologies into public education are improving in our country. This article is devoted to the importance of STEAM technology in teaching primary education subjects.